Pozycja ustrojowa rządu Republiki Estonii oraz jego rola w tworzeniu nowoczesnego państwa - Szwed, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The aim of the article is to analyze the constitutional position of the government in the Estonian political system. The parliamentary system determines the shape of the relation between the chief state authorities. A peculiar feature of Estonian governments is that they are usually formed as a coalition and are easily changed. Nonetheless, the whole political system should be regarded as stable. Currently Estonia is an example of a state that successfully applied information and communication technology to public administration. In particular the individual governments are actively working to mainstream the digitalization issue.
Constitutional position of the government of the Republic of Estonia and its role in shaping a modern state
Keywords: Estonia; executive power; government; digitalization; modern state